2016
DOI: 10.1124/jpet.116.233205
|View full text |Cite
|
Sign up to set email alerts
|

S1P Signaling and De Novo Biosynthesis in Blood Pressure Homeostasis

Abstract: Initially discovered as abundant components of eukaryotic cell membranes, sphingolipids are now recognized as important bioactive signaling molecules that modulate a variety of cellular functions, including those relevant to cancer and immunologic, inflammatory, and cardiovascular disorders. In this review, we discuss recent advances in our understanding of the role of sphingosine-1-phosphate (S1P) receptors in the regulation of vascular function, and focus on how de novo biosynthesized sphingolipids play a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 123 publications
1
46
1
Order By: Relevance
“…Shear stress exerted by flowing blood induces the production and release of S1P by the endothelium 30 , contributing to the physiological activation of S1PR1 signaling in the vasculature 6 . Pharmacological inhibition of S1PR1 in MA significantly reduced flow-mediated vasodilation 6, 11 , and lack of S1PR1 in EC in vitro and thoracic aorta in vivo reduced eNOS activation in response to shear stress 22 , implicating S1PR1 signaling in the flow-mediated vasodilation upstream of NO production.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Shear stress exerted by flowing blood induces the production and release of S1P by the endothelium 30 , contributing to the physiological activation of S1PR1 signaling in the vasculature 6 . Pharmacological inhibition of S1PR1 in MA significantly reduced flow-mediated vasodilation 6, 11 , and lack of S1PR1 in EC in vitro and thoracic aorta in vivo reduced eNOS activation in response to shear stress 22 , implicating S1PR1 signaling in the flow-mediated vasodilation upstream of NO production.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, we reported that endothelial derived S1P has a great impact on systemic BP regulation via S1PR1-S1P-eNOS autocrine signaling 6, 11, 22 . Shear stress exerted by flowing blood induces the production and release of S1P by the endothelium 30 , contributing to the physiological activation of S1PR1 signaling in the vasculature 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1P activation of endothelial S1P receptors induces eNOS-dependent NO secretion and vasodilation (48). We showed that ApoM-Fc–S1P potently reduced blood pressure in a sustained manner (~190 hours) in AngII-induced hypertensive mice.…”
Section: Discussionmentioning
confidence: 99%